2017
DOI: 10.1016/j.molimm.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

SERPINB2 is regulated by dynamic interactions with pause-release proteins and enhancer RNAs

Abstract: The SERPINB2 gene is strongly upregulated in inflammatory states. In monocytes, it can constitute up to 1% of total cellular protein. It functions in protection from proteotoxic stress and plays a role in angioedema. The purpose of this study was to define the roles of enhancer RNAs embedded in the SERPIN gene complex. We found that the upstream enhancer RNAs upregulated SERPINB2 and the enhancer RNAs were expressed prior to those of SERPINB2 mRNA. Studies of the SERPINB2 promoter demonstrated the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 65 publications
(69 reference statements)
2
40
0
Order By: Relevance
“…eRNA knockdown studies have demonstrated important roles for individual eRNAs in the regulation of their target genes ( Supplementary Table 1). Additional studies have shown that exogenous overexpression of eRNAs leads to an increase in their respective mRNA targets (Alvarez-Dominguez et al, 2017;Shii et al, 2017;Jiao et al, 2018). These studies have provided the bulk of evidence implicating a directly causal role for eRNA, rather than the act of transcription, in the association between enhancer and mRNA transcription.…”
Section: Biological Functions Of Erna Erna As Regulators Of Gene Exprmentioning
confidence: 99%
See 4 more Smart Citations
“…eRNA knockdown studies have demonstrated important roles for individual eRNAs in the regulation of their target genes ( Supplementary Table 1). Additional studies have shown that exogenous overexpression of eRNAs leads to an increase in their respective mRNA targets (Alvarez-Dominguez et al, 2017;Shii et al, 2017;Jiao et al, 2018). These studies have provided the bulk of evidence implicating a directly causal role for eRNA, rather than the act of transcription, in the association between enhancer and mRNA transcription.…”
Section: Biological Functions Of Erna Erna As Regulators Of Gene Exprmentioning
confidence: 99%
“…Extracellular stimuli drive signaling pathways which remodel chromatin and alter eRNA and mRNA expression (Kaikkonen et al, 2013;Heward et al, 2015). eRNA transcription occurs very early in the gene transcription process, preceding mRNA expression from adjacent cis loci (Schaukowitch et al, 2014;Arner et al, 2015;Kim et al, 2015;Baillie et al, 2017;Shii et al, 2017;Tyssowski et al, 2018). Indeed, the ubiquitous and early production of eRNAs makes them an excellent marker for segregating active versus quiescent enhancers, which is discussed in greater detail below (Andersson et al, 2014a;Tyssowski et al, 2018).…”
Section: Cellular Production Of Ernamentioning
confidence: 99%
See 3 more Smart Citations